RONI SARWANI Batik Motif Design Development Through the Transformation of the Mahligai Temple, Muara Takus Temple in Kampar District - roni sarwani; B Budiwirman (Universitas Negeri Padang Padang, Indonesia, 2023)
Roni Sarwani, 2022. Transformation of the Mahligai Stupa of Muara Takus Temple as a Batik Motif Design in Kampar Regency. Thesis proposal. Padang State University Postgraduate Program. Based on the existing conditions, it is known that the root of the problem in the field of Malay batik product design in the form of Batik Motif Design Development through the Transformation of the Mahligai Stupa of Muara Takus Temple in Kampar Regency, is due to a lack of human resources who have the potential to be creative and innovative in creating batik motif designs by transforming the Stupa Mahligai Muara Takus Temple in Kampar Regency. So that this condition resulted in the quality of community resources to be low. To improve the quality of community resources in Kampar Regency, efforts have been made to develop regionally distinctive batik motif designs. The goal to be achieved in the development of this batik motif design is the preservation of Malay culture in the transformation of cultural objects as a typical batik motif design for the Kampar Regency area. The type of this research is Batik Motif Design Development Research developed using four-D models. Data collection was carried out by validating and testing the developed product. The design will be designed, validated by experts, to determine the practicality and effectiveness of the motif designs developed. Batik motif designs were produced through the transformation of the Mahligai Stupa of Muara Takus Temple in Kampar Regency as a valid effort to preserve local culture. Based on the pre-test conducted in the batik motif design process, it is known that its implementation is in the very practical category. The response from the local community is urgently needed in the transformation of the batik motif design of the Mahligai Stupa of Muara Takus Temple into a batik motif design in Kampar Regency which is developed into positive results. Pre-observation results showed good results. In addition, this research also produced two training products in the form of 1) Batik Motif Design Development Book, 2) batik products in the form of batik cloth. Keywords: Design of Batik Motifs, Transformation of the Mahligai Stupa of Muara Takus Temple, Batik in Kampar Regency.